1976
DOI: 10.1021/bi00648a037
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight deoxyribonucleic acid polymerase from crown gall tumor cells of periwinkle (Vinca rosea)

Abstract: A high molecular weight (6 S) plant DNA polymerase from axenic Vinca rosea tissue culture cells has been purified 2200-fold and characterized. The enzyme has a molecular weight of 105 000 (+/-5000). Sodium dodecyl sulfate-acrylamide gel electrophoresis of the purified enzyme yields polypeptide subunits having molecular weights of 70 000 and 34 000. The purified enzyme has a pH optimum of 7.5; a cation requirement optimum of 6 mM Mg2+ or 0.5 mM Mn2+; an apparent requirement for Zn2+; a Km of 1 muM for dTTP; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Other authors have described polymerases of the/3 type based on the dubious criteria of a strong affinity of the enzyme to chromatin (18,13). Some investigators have proposed that plants do not possess a low molecular weight DNA polymerase, since this kind of enzyme could not be detected in crude wheat extracts and in Vinca rosea (19,7). The absence of activity in wheat can be explained by the observation that the low molecular weight DNA polymerase present in the flowthrough of a DEAE-cellulose column can only be detected if an inhibitor is previously eliminated by phosphocellulose chromatography.…”
Section: Dna Polymerases Found In Plant Cellsmentioning
confidence: 99%
“…Other authors have described polymerases of the/3 type based on the dubious criteria of a strong affinity of the enzyme to chromatin (18,13). Some investigators have proposed that plants do not possess a low molecular weight DNA polymerase, since this kind of enzyme could not be detected in crude wheat extracts and in Vinca rosea (19,7). The absence of activity in wheat can be explained by the observation that the low molecular weight DNA polymerase present in the flowthrough of a DEAE-cellulose column can only be detected if an inhibitor is previously eliminated by phosphocellulose chromatography.…”
Section: Dna Polymerases Found In Plant Cellsmentioning
confidence: 99%
“…DNA polymerases which share some, but not all, of the properties of the animal and yeast a-type DNA polymerases have been reported from cauli¯ower (Fukasawa et al 1980), maize (Coello et al 1992;Coello-CoutinÄ o et al 1994;Coello and Va zquez-Ramos 1995), pea (Chivers and Bryant 1983;Bryant et al 1992), periwinkle (Gardner and Kado 1976), rice (Amileni et al 1979), spinach (Misumi and Weissbach 1982), sugar beet (Tymonko and Dunham 1977), turnip (Dunham and Bryant 1986) and wheat (Castroviejo et al 1979;Graveline et al 1984;Laquel et al 1990aLaquel et al ,b, 1994. Only a few of these studies have reported on associated primase activities.…”
Section: Introductionmentioning
confidence: 99%
“…In 1975 they purified and partially characterized three cytoplasmic DNA pols (A, B and C) from ungerminated wheat embryos and another DNA pol from purified mitochondria that behaves like DNA pol B. 102 Considering the possibility that cytoplasmic DNA pol B was a release product of broken mitochondria, on the basis of chromatographic separation, template-specificity and enzyme properties, the conclusions emerging from their and others' studies [103][104][105][106][107] were that: 1) plants might contain two high MW DNA pols; 2) such enzymes possessed associated exonuclease activities like those of bacterial DNA pols, and 3) that no low MW DNA pol analogous to animal DNA pol b was found in plant cells.…”
Section: Plant Cell Dna Polymerasesmentioning
confidence: 99%